Marketing Margins for Imported and Local Rice in Akure, Ondo State, Nigeria: A Comparative Analysis (JOURNAL OF ADVANCES IN AGRICULTURE, 2018)
The study was carried out in Akure, Ondo State. Multi stage and sampling technique procedure was used which involved purposive and random sampling methods in selecting the respondents with the aid of well-structured questionnaire with interview schedule. Descriptive statistical analysis, budgetary techniques, marketing margin analysis as well as Gini-coefficient and Herfindahl Hirshman Index was used for the analysis of variables. The result reviewed that more of the imported brands of rice in all the four market sampled than the local rice, with local rice margin as percentage of total marketing margin (16.95%) lower than that of local rice (17.78%) the average marketing efficiency of 349.91% and 467.89% were obtained from imported and local rice respectively while the Gini- coefficient (GC) Herfindahl Hirshman Index (HHI) values of 0.68 and 0.28 were obtained reviewing that rice marketing were highly concentrated with non-competitive practices showing disparity in earnings. The prevailing duration stocks were held in shops by trader was three to four weeks and the major sources of obtaining market information was mobile phone. The study recommends provision of storage facilities for the traders and also improvement in the quality of local rice with policy implementation that discourage importation of commodity as a way out of boosting and encouraging local rice production and its consumption.